Does Cross-Border-Establishment Improve Competition and Performance of Indonesia’s Financial Sector? - Heni Nugraheni; Satrio Nugroho; Azizah Surayya Warman (Otoritas Jasa Keuangan, 2023)
This study examines the effects of cross-border establishment of financial institutions on competition level in Indonesia’s financial sector. We use sample data on all conventional banks, securities firms, life and general insurance companies from 2013-2020. To measure competition, we use Lerner index, Boone indicator and Panzar-Rosse. Our analysis shows that the entry of foreign financial institutions may increase the competition in the financial sector. Further analysis shows that the increasing competition have positive impact to profitability and intermediation, reflected by the return on asset, loan ratio, transaction value, and insurance premium income to total asset ratio. However, foreign financial firms tend to have higher market power compared to domestic counterparts due to the efficiency in doing their businesses. Hence, domestic financial institutions need to boost efficiency, particularly through the adaption of technology and capacity enhancement of human resources, in order to compete with more advanced foreign financial firms.